Autopsy Findings in an Infant with Primary Hyperoxaluria (Type-1) - Kumar, Aman; Kinra, Prateek; Kashif, A W (Annals of Pathology and Laboratory Medicine, 2020)
Histopathological findings in oxalosis patient are limited in the literature, although it has high mortality. Oxalosis, which is defined as deposition of calcium oxalate crystals in tissues, is the final stage of various hyperoxaluric syndromes. It is often missed and is rare. The diagnosis is often delayed, since it requires special laboratory tests for establishing the diagnosis. Kidneys, blood vessel walls, and bones are the major sites for crystal deposition. We present an infant autopsy case of primary hyperoxaluria, type 1. Diagnosis was established with genetic testing. On autopsy, calcium oxalate crystals which were refringent to polarized light were found in both kidneys.